Self-Efficacy, Resilience, and Loneliness in People with Schizophrenia - Wijayanti, Diyan Yuli; Sarjana, Widodo; Astuti, Halimah Wenny Yulina; Sari, Sri Padma (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Self-efficacy and resilience have been associated with loneliness in schizophrenia. Studies reported that people with schizophrenia have low self-efficacy, resilience, and experience a greater level of loneliness, which could lead to worsening symptoms. However, inpatient and outpatients’ differences in these variables have rarely been investigated. This study aimed to compare self-efficacy, resilience, and loneliness among people with schizophrenia from outpatients and inpatients. A total of 130 patients diagnosed with schizophrenia were included in this study. The data were collected using the socio-demographic questionnaire, the General Self-Efficacy Scale (GSE), Connor-Davidson Resilience Scale 10 (CD-RISC 10), and the University of California Los Angeles (UCLA) Loneliness Scale Version 3. The Chi-Square, Mann-Whitney, and the t-test were used for data analysis. The results indicated that inpatient has higher self-efficacy and resilience than outpatients. Interestingly, inpatient significantly has lower loneliness than outpatients. The findings support the evidence of psychological differences in schizophrenia and provide a better understanding of different settings with this diagnosis. In the clinical practice, these results suggest developing interventions to enhance resilience and self-efficacy in schizophrenia. Keywords: Loneliness, Resilience, Self-Efficacy, Schizophrenia